Degradation of 2, 4-Dinitrophenol using persulfate activated by Cu2+ in photocatalytic system (UV/SPS/Cu2+) from aqueous solution: optimisation and operational parameters. Issue 3 (19th February 2022) - Pasalari, Hasan; Esrafili, Ali; Yegane Badi, Mojtaba; Farzadkia, Mahdi
ABSTRACT: The present study was developed to model and optimise 2, 4-Dinitrophenol (2, 4-DNP) degradation from aqueous solution using UVC/SPS/Cu 2+ system based on the response surface methodology (RSM) and Box-Behenken (BBD) approach. A high removal efficiency (92.75%) and total organic carbon (TOC) reduction (61.5%) were obtained under optimum conditions, i.e. (Time = 59 min, SPS Con. = 58.74 mg/L, Cu 2+ Con = 14.12 mg/L, pH = 11, Initial Con = 6 mg/L). Quenching experiments confirmed that sulphate radicals were predominant radical species for 2-4-DNP degradation. The effect of CO3 − on 2, 4-DNP degradation was more complicated than other aquatic background anions. Finally, the performance of UVC/SPS/Cu 2+ system for 2, 4-DNP treatment in different aquatic solutions: tap water, surface runoff, treated and raw wastewater were found to be 89.76%, 81.65%, 51.22% and 75.94%, respectively.